Stem cell maintenance in the adult mammalian hippocampus: a matter of signal integration? - Schwarz, Tobias J.; Ebert, Birgit; Lie, Dieter Chichung (Developmental Neurobiology, 2012)
The continuous generation of new neurons from stem cells in the hippocampal dentate gyrus is considered an important contributor to hippocampal plasticity. A prerequisite for the life-long generation of new dentate granule neurons is the maintenance of the neural stem cell pool. A number of essential molecular regulators and signals for hippocampal neural stem cell maintenance have been identified, but how these pathways interact to prevent precocious differentiation or exhaustion of the stem cell pool is currently unknown. Here, we summarize the current knowledge on the molecular regulation of the hippocampal stem cell pool and discuss the possibility that signal integration through Notch signaling controls stem cell maintenance in the adult hippocampus.
EVALuna2:26315